Drivers of innovation capacity and consequences for Open Innovation - Walter, Cicero Eduardo (2022)
The main objective of the present research is to identify the knowledge flows responsible for promoting the innovation capacity of Portuguese companies. Specifically, we intend to identify which variables influence Portuguese innovation capacity from a macro and micro perspective, so that we can establish possible ways to promote open innovation (OI) in Portugal since Portuguese companies have little maturity in terms of open innovation when compared to companies in other countries of the European Union. To achieve this goal, the methodological design used consisted of two phases. In the first phase, a literature review was conducted to identify the main variables associated with innovation performance. After identifying the most influential variables in the literature, in a second phase, data were collected through three distinct databases, namely Pordata, the Portuguese Tax and Customs Authority, and SABI. To identify the most influential variables in the Portuguese innovation capacity, the multivariate multiple regression technique based on the ordinary least square (OLS) method was applied. The results of the present research bring empirical evidence that researchers dedicated to R&D from non-profit institutions (i.e., inbound OI) and researchers from firms (i.e., outbound OI) exert a significant influence on innovation capacity so the development of an optimal strategy for the strengthening of open innovation by Portuguese firms should take into account the use and combination of these two specific knowledge flows. In this sense, the originality of this research lies in the fact that it is the first attempt to understand the possible implications of the determinants of innovation capacity on open innovation, from an exploratory study concerning the flows of knowledge.